Pulsed Dose Rate (PDR – BT) brachytherapy in treatment of breast cancer - Skowronek, Janusz (Contemporary Oncology/Współczesna Onkologia, 2007)
Breast conserving surgery (BCS) and radiotherapy (EBRT) of the conserved breast became widely accepted in the last decades for the treatment of early invasive breast cancer. The standard technique of RT after breast conservation is to treat the whole breast up to a total dose of 45 to 50 Gy. Initially brachytherapy for breast cancer was used in addition of external radiation to boost a portion of the breast to higher doses. However, over the past 10 years, the application of brachytherapy in breast cancer has changed. In early stage breast cancer, research has shown that the area that requires radiation treatment to prevent the cancer from returning is the breast tissue that surrounds the area where the initial cancer was removed. Because this typically includes only a part of the breast, brachytherapy is now being used to treat the targeted portion of the breast and as a result allows accelerated delivery of the radiation dose so that treatment is completed in four to five days. Another indications for PDR – BT as a part of treatment in locally advanced breast cancer or as a palliative treatment are discussed in the paper, too. Preliminary results with PDR – BT boost technique are promising. However, more experience and longer follow-up are required to define whether these methods might improve local tumor control for breast cancer patients. In this article the current status, indications, technical aspects and published results of PDR brachytherapy (PDR – BT) in breast cancer treatment are reviewed